Differentiation Strategies in Qur'an Memorization: A Case Study at Daarul Yusr Islamic Boarding School - Aufa, Nisa; Suresman, Edi; Islamy, Mohammad Rindu Fajar (TAFSE: Journal of Qur'anic Studies, 2024)
The rapid growth of Islamic education in Indonesia, particularly in the tahfidz Al-Qur'an program, has seen significant progress, with more than 25,000 educational institutions registered by 2024. However, not all institutions produce high-quality hafidz, largely due to the diverse abilities of students, which are influenced by their educational backgrounds and memorization methods. This study focuses on the strategies employed by students in memorizing the Qur'an and the practical implementation of these strategies. The research aims to identify effective memorization methods in tahfidz programs and evaluate their impact on the quality of memorization. Using a qualitative approach with a case study design at the Daarul Yusr Al-Qur'an Islamic Boarding School, data were collected through observation, interviews, and documentation, then analyzed thematically. The findings reveal that 10 students successfully memorized 30 juz of the Qur'an. Additionally, the memorization process contributed to enhancing students' discipline and self-confidence. These results affirm that employing a differentiated approach in memorization not only improves the quality of memorization but also positively influences students' character. This study is expected to serve as a reference for Islamic educational institutions in addressing challenges in tahfidz education and developing curricula tailored to individual student needs.